Yield and Palatability of Potential Indigenous Leafy Vegetable of Cold Arid trans-Himalayan Ladakh, India - Rinchen, Tsewang; Singh, Narendra; Maurya, Samar Bahadur (Defence Life Science Journal, 2018)
Not much attention has been paid to a wide range of indigenous leafy vegetables that can grow in high altitude harsh climatic conditions with minimal care. Therefore, a study was carried out on yield potential and palatability of indigenous leafy vegetables (ILV) that grows in trans-Himalayan Ladakh. Seven ILV viz. Fagopyrum tataricum, Rumex patientia, Fagopyrum esculentum, Amaranthus cruentus, Malva vertisilester, Lepidium latifolium and Atriplex hortensis that are being used by native people of Ladakh were recorded for their morphological characters, earliness, yield and other consumer preference traits. The highest yield was recorded for A. hortensis (1.80±0.06 kg/m2). The study suggested that A. hortensis and A. crunteus have high palatability and are most preferred by the consumers. Yield potential of the cold hardy A. hortensis is significantly higher and it is an early maturing crop. Therefore, detail studies on A. hortensis are required, and efforts need to be made for large scale cultivation of the species.